Higher spring phenological sensitivity to forcing temperatures of Asian compared to European tree species under low and high pre-chilling conditions - Walde, Manuel G.; Wu, Zhaofei; Fox, Tom; Baumgarten, Frederik; Fu, Yongshuo H.; Wang, Shuxin; Vitasse, Yann (Frontiers in Forests and Global Change, 2022)
Spring phenology of temperate trees is driven by winter chilling, spring forcing temperature and photoperiod.However, there is a lack in studies that tried to disentangle the interaction of those factors given that requirements of each factor varies greatly dependent on species. Therefore, we investigated the interaction of different pre-chilling conditions, photoperiods and a broad range of forcing temperatures. In addition, we investigated whether phylogentic related species show a distinct reaction to those cues dependent on predictivity of winter-spring transition of the local climate. We found that temperature is the most important driver of spring phenology for most species investigated, whereas photoperiod mostly if at all plays a subordinate role regardless of origin. Further, the tree species growing in a more predictable climate reacted faster to forcing temperature. Thus, our results suggest that deciduous trees may have adapted their chilling and forcing requirements to the predictability of winter-spring transition and late spring frosts.